Cell-Type-Specific Regulon Activity Alterations Across Alzheimer’s Disease, Parkinson’s Disease, and Frontotemporal Dementia - Mohamed, Sherine Khalafalla Saber Ahmed (AUC Knowledge Fountain, 2026)
Alzheimer’s disease (AD), Parkinson’s disease (PD), and frontotemporal dementia (FTD) exhibit distinct but partially overlapping molecular features. However, the extent to which cell-type-specific transcription factor (TF)-associated regulatory alterations recur across these disorders remains incompletely characterized. In this study, single-nucleus RNA-seq datasets from AD, PD, FTD, and matched controls were analyzed to investigate TF-associated gene regulatory network alterations across the diseases. Regulon activity was inferred using pySCENIC and quantified with AUCell, and disease-associated differences were assessed within matched cell types and brain regions. Several regulons showed recurrent disease-associated activity differences across disease contexts, with the strongest patterns observed in astrocytes and oligodendrocytes. Regulon specificity score (RSS) analysis showed partial overlap among top-ranked cell-type-specific regulons across diseases and supported the relevance of some differentially active regulons in their corresponding cell types. Connection Specificity Index (CSI)-based network analysis organized the regulons into distinct co-activity modules, with hub regulons occupying central positions within the broader regulatory architecture. Functional enrichment analysis and literature-based contextualization linked these regulons to processes relevant to neurodegeneration, including proteostasis, myelin-related regulation, neuronal communication, and stress-associated transcriptional remodeling. Exploratory gene–drug screening further showed that several compounds interacting with candidate regulon-associated TFs had prior clinical or preclinical evidence in AD-, PD-, and/or FTD-related studies, with some supported in more than one disease context. However, whether these TFs contribute to the reported drug effects remains to be determined. Overall, these findings suggest that AD, PD, and FTD may involve partially convergent, cell-type-dependent alterations in TF-associated regulon activity. Although the results are based on inferred regulon activity and require validation using independent datasets and orthogonal experimental approaches, they provide a framework for prioritizing TFs, regulatory programs, and candidate compounds for future mechanistic and therapeutic investigation.